Challenges And Perceptions Of Social Service Professionals On The Effectiveness Of Gender Based Violence Services And Programmes In Cape Town - Nojilana, Somila (Department of Social Development, 2024)
Gender-based violence is an umbrella term which refers to harm that is inflicted on a victim by a perpetrator because of the victim's gender. It is a concern globally and in South Africa. Studies conducted in South Africa indicate that the country has the highest report of genderbased violence cases globally, the level of intimate femicide in South Africa is 5 times more than the global average. This research focuses on exploring the challenges experienced and the effectiveness of services and programmes offered to gender based violence victims from the perspective of social service professionals namely social workers and social auxiliary workers who play a pivotal role in service provision. Previous research fails to address challenges social services professionals encounter which prohibit them to provide quality services to clients. The research uses the informed experiences of social workers and social auxiliary workers who work as mediators between clients and external government resources. The aim of this qualitative, exploratory research was to understand how gender-based violence programmes and services can be improved by highlighting challenges which form barrier to ideal service provision. Non-probability purposive sampling technique was utilised to recruit and explore social service professionals from the NGO sector in Cape Town over 5 communities namely Hout Bay, Masiphumelele, Ocean View, Mooresburg and Paarl. Data was collected through individual semi-structured interviews and analysed by means of a thematic analysis.